Latent profile analysis of operating room nurses’ occupational fatigue and its relationship with attentional control - Jiao Zhai; Shuangying Gong; Feng Chen; Ping Zheng; Wanlin Liu; Xiaoxia Dai; Caixia Xie (BMC Nursing)
Abstract Background Occupational fatigue in operating room nurses may influence their attentional control. However, few previous studies have explored the correlation between occupational fatigue and attentional control in operating room nurses. To better understand operating room nurses’ occupational fatigue and its relationship with attentional control, this study aimed to identify the latent profiles and their factors that influence operating room nurses’ occupational fatigue as well as differences in attentional control across each latent profile. Methods A cross-sectional study was conducted from May 2024 to July 2024, and a total of 386 operating room nurses were recruited from 6 hospitals in Chengdu. The participants completed the Occupational Fatigue Scale and the Attentional Control Scale. Latent profile analysis (LPA) was employed to identify latent profiles of occupational fatigue among operating room nurses. The predictors of occupational fatigue in different latent profiles were assessed via multinomial logistic regression analysis. One-way ANOVA and the Kruskal–Wallis test were used to compare the scores on the attentional control scale for each latent profile of nurses’ occupational fatigue. Results This study identified three latent profiles of operating room nurses’. occupational fatigue: the “low-fatigue/high-recovery group” (n = 80, 21.2%), the “high-fatigue/low-recovery group” (n = 113,29.3%) and the “moderate-fatigue/mod-erate-recovery group” (n = 193, 49.4%). The results of the multinomial logistic regression analysis suggested that age, work experience, educational level and monthly income were predictors of operating room nurses’ occupational fatigue. There were significant differences in attentional control among the different pr-ofiles of occupational fatigue (P < 0.001). The scores for attentional focus were. Significantly different across each profile (P < 0.001), whereas the scores for at-tentional shift were not different across profiles (P = 0.342). Conclusions Operating room nurses’ occupational fatigue can be divided into three latent profiles. Reducing chronic and acute fatigue while enhancing intershift recovery can improve nurses’ attentional control and improve the overall service quality of the hospital. Nursing managers should identify operating room nurses who are at risk and implement targeted interventions to reduce occupational fatigue. Trial registration This study does not involve clinical trials or interventional procedures and therefore does not meet the criteria for clinical trial registration.